THE ROLE OF ZAKAT COMMUNITY DEVELOPMENT IN THE ADVANCEMENT OF SMART FARMING TO SUPPORT SUSTAINABLE DEVELOPMENT IN BONDOWOSO REGENCY - Abdul Mu'is; Moch. Chotib; Nikmatul Masruroh (Adisam Publisher, 2025)
Islam, as a religion embodying rahmatan lil 'alamin (mercy to all creation), strongly emphasizes the preservation of human welfare, including faith, life, mental health, lineage, and property. This qualitative study, grounded in a post-positivist paradigm and phenomenology, explores the lived experiences of community members involved in smart farming empowerment in Bondowoso Regency. Focusing on the innovative